Letter C-Based Land Rights Verification in the Implementation of PTSL in Patemon Village (Indonesian Journal of Agrarian Law, 2026)
According to Article 19 of Law Number 5 of 1960 regarding the Primary Agrarian Laws (UUPA), land registration is an important tool for guaranteeing legal certainty and giving protection to land tenure. In the process of land registration, including the CSLR Programme (Complete Systematic Land Registration), the way of proving ownership on unregistered land is by reference to village administrative records (Letter C). This research will examine the validity of using Letter C in proving land ownership for the purposes of CSLR in Patemon Village, along with identifying issues and solutions to registering land in this manner. The research used is of a normative legal nature, using a Legislative Approach, supported by empirical studies involving case studies, and interviews with both village officials and the Land Office. The findings showed that although Letter C is not the same as Land Certificate, it can be utilised as an identity ( basis / title) for land ownership and can be added with additional documentation and needed to be confirmed by the relevant authorities for first-time registrations. Letter C is currently accepted as proof of land ownership in Patemon for the CSLR programme.